Fidelización de clientes y su influencia en el posicionamiento de financiera Proempresa en la ciudad de Huamachuco - 2017 - Gómez Valderrama, Elquin José (2019)
The general objective of this research was to determine how customer loyalty influences the positioning of the Proempresa financial company in the city of Huamachuco - 2017. The problem was: How customer loyalty influences Financial positioning Proempresa in the city of Huamachuco - 2017?. The population was formed by the 450 clients up to the present, whose sample was 59 clients; the data collection technique used was the survey whose instrument was the questionnaire. The research design that was used was nonexperimental transectional type correlational. After obtaining the respective results and being analyzed, the corresponding discussion was carried out, thus demonstrating the study hypothesis that "Customer loyalty has a positive influence on the positioning of Financiera Proempresa in the city of Huamachuco - 2017 ". The main conclusion is that customer loyalty has a positive influence on the positioning of the Proempresa financial company in the city of Huamachuco, as shown by the Pearson Correlation Coefficient (r = 0.765), both variables also qualify. At the medium level, which indicates that if the independent variable has positive factors they will influence the same direction in the dependent variable. Therefore, it is recommended that attention be paid to customer requirements and provide good quality service; as well as committing staff to deliver a good service, and provide incentives that they expect to receive; in order to attract more customers and thus gain a better position in the sector.